Shape- and Size-Selective Preparation of Hectorite-Supported Ruthenium Nanoparticles for the Catalytic Hydrogenation of Benzene - Süss-Fink, Georg; Khan, Farooq-Ahmad; Boudon, Julien; Spassov, Vladislav (My University, 2009)
The cationic organometallic aqua complexes formed by hydrolysis of [(C6H6)2RuCl2]2 in water, mainly [(C6H6)Ru(H2O)3]2+, intercalate into white sodium hectorite, replacing the sodium cations between the anionic silicate layers. The yellow hectorite thus obtained reacts in water with molecular hydrogen (50 bar, 100 °C) to give a dark suspension containing a black hectorite in which large hexagonally shaped ruthenium nanoparticles (20–50 nm) are intercalated between the anionic silicate layers, the charges of which being balanced by hydronium cations. If the reduction with molecular hydrogen (50 bar, 100 °C) is carried out in various alcohols, spherical ruthenium nanoparticles of smaller size (3–38 nm depending on the alcohol) are obtained. In alcohols other than methanol, the reduction also works without H2 under reflux conditions, the alcohol itself being the reducing agent; the ruthenium nanoparticles obtained in this case are spherical and small (2–9 nm) but tend to aggregate to form clusters of nanoparticles. Whereas the ruthenium nanoparticles prepared by reduction of the yellow hectorite in refluxing alcohols without hydrogen pressure are almost inactive, the nanoparticles formed by hydrogen reduction catalyze the hydrogenation of benzene to give cyclohexane under mild conditions (50 °C) with turnover frequencies up to 6500 catalytic cycles per hour, the best solvent being ethanol.
Keywords: Ruthenium nanoparticles; Ruthenium-modified hectorite; Benzene hydrogenation